2017
DOI: 10.1111/jpi.12399
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin prevents obesity through modulation of gut microbiota in mice

Abstract: Excess weight and obesity are severe public health threats worldwide. Recent evidence demonstrates that gut microbiota dysbiosis contributes to obesity and its comorbidities. The body weight-reducing and energy balancing effects of melatonin have been reported in several studies, but to date, no investigations toward examining whether the beneficial effects of melatonin are associated with gut microbiota have been carried out. In this study, we show that melatonin reduces body weight, liver steatosis, and low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
188
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 241 publications
(218 citation statements)
references
References 65 publications
(77 reference statements)
21
188
1
8
Order By: Relevance
“…Improvements in intestinal barrier dysfunction were substantial at the high dose (40.0 mg/kg) of MT supplementation (SD + 2MT group). Previous studies have reported that MT treatment significantly changes the richness, diversity and composition of the gut microbiota in both murine models of obesity and weanling stress . These results indicate that MT suppression plays a crucial role in SD‐induced intestinal homoeostasis disorder.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Improvements in intestinal barrier dysfunction were substantial at the high dose (40.0 mg/kg) of MT supplementation (SD + 2MT group). Previous studies have reported that MT treatment significantly changes the richness, diversity and composition of the gut microbiota in both murine models of obesity and weanling stress . These results indicate that MT suppression plays a crucial role in SD‐induced intestinal homoeostasis disorder.…”
Section: Discussionmentioning
confidence: 60%
“…Studies have reported that the MT concentration is approximately 2000‐11 000 pg/mL in the bile to prevent small intestinal epithelial injury . Previous compelling investigations have demonstrated that MT influences the swarming and motility of Enterobacter aerogenes, the richness and diversity of the mouse intestinal microbiota, the ratio of Firmicutes to Bacteroidetes (F:B) and the abundance of Akkermansia . However, few clinical or experimental studies have evaluated the effect of MT on gut microbiota dysbiosis and the loss of intestinal mucosal integrity induced by SD.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin plays a vital role in the amelioration of metabolic disorders in various organs/tissues, including adipose tissue and liver . Although previous studies have already discussed that melatonin enables obesity‐induced dysmetabolism of adipose tissue and hepatic steatosis to be reversed, little focused on the regulatory efforts of melatonin on their crosstalk under HFD‐induced obese condition.…”
Section: Discussionmentioning
confidence: 99%
“…Such anorectic effect, however, was found only in nondiabetic Wistar, but not in diabetic rats. In support to this view, a previous work has demonstrated that melatonin prevents diet-induced obesity in mice via counteracted changes in the composition of the microbiome (ie, dysbiosis), decrease in low-grade inflammation and oxidative stress, dyslipidaemia, as well as stimulation of browning in inguinal subcutaneous adipose tissue and improvement of insulin resistance 40. Among peripheral tissues, gut is a candidate to be affected by melatonin treatment.…”
mentioning
confidence: 86%